Good Extractive Governance Sebuah Gagasan untuk Kesejahteraan Masyarakat Wilayah Pertambangan di Indonesia - Mi’rojul Huda; Novy Setia Yunas (Research and Development Agency Ministry of Home Affairs, 2017)
The mining problem has been an irony for the society, not only to gain the welfare of the economic impacts of the mining business, but to create new problems and conflict in the society. The main objective of this study is to develop a good extractive governance idea for improving the welfare of society in mining areas. This study uses a qualitative approach with descriptive research method that uses data collection techniques in-depth interviews and field observations. As for the findings of this paper, among others, the existence of natural resources in the form of oil and natural gas has caused more disasters such as conflicts, environmental disasters to economic gaps in society due to poor management. But ideally, the oil and gas industry will contribute maximally to improving the welfare of the society if managed properly. So as to maximize the potential of existing resources, there needs to be strong commitment from various parties to establish a good governance in the extractive industry area (Good Extractive Governance). This could start with the government’s commitment to oil and gas sovereignty and other extractive industries. And the existence of participatory planning in potential management in the region.